A Study and Analysis of the Treatment of Mexican Unaccompanied Minors by Customs and Border Protection. (June 2020) - Coulter, Kiera; Sabo, Samantha; Martínez, Daniel; Chisholm, Katelyn; Gonzalez, Kelsey; Bass Zavala, Sonia; Villalobos, Edrick; Garcia, Diego; Levy, Taylor; Slack, Jeremy
Executive Summary: The routine human rights abuses and due process violations of unaccompanied alien children (UAC) by US Customs and Border Protection (CBP) have contributed to a mounting humanitarian and legal crisis along the US–Mexico border. In the United States, the treatment of UAC is governed by laws, policies, and standards drawn from the Flores Settlement, the Trafficking Victims Protection Reauthorization Act (TVPRA), and CBP procedures and directives, which are intended to ensure UAC's protection, well-being, and ability to pursue relief from removal, such as asylum. As nongovernmental organizations and human rights groups have documented, however, CBP has repeatedly violated these legal standards and policies, and subjected UAC to abuses and rights violations. This article draws from surveys of 97 recently deported Mexican UAC, which examine their experiences with US immigration authorities. The study finds that Mexican UAC are detained in subpar conditions, are routinely not screened for fear of return to their home countries or for human trafficking, and are not sufficiently informed about the deportation process. The article recommends that CBP should take immediate steps to improve the treatment of UAC, that CBP and other entities responsible for the care of UAC be monitored to ensure their compliance with US law and policy, and that Mexican UAC be afforded the same procedures and protection under the TVPRA as UAC from noncontiguous states.